The Potential Integration of Informal to Formal Workers in Muara Fajar Landfill (TPA) Pekanbaru with the Circular Economy Concept - Rizky Syahputra; Gabriel Andari Kristanto; Astryd Viandila Dahlan (Publikasi Indonesia, 2025)
Waste is a serious problem in developing countries due to infrastructure limitations, one of which is the city of Pekanbaru. The existence of the landfill triggered the arrival of informal workers such as scavengers to collect waste as recycled product materials. Most scavengers live below the poverty line, even though scavengers have a role in restraining the waste generation rate in landfills. This study aims to analyze the potential integration of scavengers in the Muara Fajar Landfill Area with formal workers using integrated waste management,